Analisis Kinerja Operasi pada Masa Pandemi Covid-19 dengan Penerapan Total Quality Management (TQM) dan Supply Chain Management (SCM) Di UMKM Kota Tasikmalaya - Suci Putri Lestari; Arga Sutrisna (Universitas Batanghari Jambi, 2021)
This research was conducted to analyze the application of total quality management (TQM) and supply chain management (SCM) in UMKM in Tasikmalaya city to improve the performance of UMKM operations. And to understand which methods can improve the performance of UMKM operations. Using the probability sampling method by spreading questionnaires against 90 UMKM who apply the TQM and SCM methods in the operation process. Hypothesis tests using multiple regressions with research results have significant influences on the application of TQM and SCM to improve operatic performance during the covid-19 pandemic in UMKM in tasikmalaya city.